XML development with plug‐ins as a service. (9th December 2013) - Karus, S.; Garbervetsky, Diego; Kim, Sunghun
SUMMARY Extensible Markup Language (XML) has quickly become a mainstream language in software development. Not only is it used for message and document interchange, it is also used to define application logic and interfaces. However, modern general purpose integrated development environments have rather limited support for XML development. The wide variety of XML‐based languages makes it a challenge to build tools for comprehensive support of XML development. In this paper, we present extensions to a library exposed as an add‐in for Microsoft Visual Studio and a command line tool to improve the development experience by providing access to subscribable service‐based pluggable helper tools. The architecture of the solution allows easier publishing and deployment of the tools, minimising the exposure of development data to third parties and providing service providers with much needed tool usage and development process data. The tools offer developers new means to check their files against good and bad practices, automatically fix errors in XML or improve the files' conformance with development guidelines, current state of project with other projects, or run service queries to estimate their projects future progress. Copyright © 2013 John Wiley & Sons, Ltd.